Uma análise sobre a formação do Quilombo do Maicá, e a construção de sua identi- dade em meio a singularidades e impactos ambientais. - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
The present work addresses the socio-territorial impacts and the construction of quilombola territorial identity as a result of urban influence, more specifically in the Metropolitan Region of Santarém/-PA. The panorama in the quilombola territory is influenced by municipal actions based on the analysis of the master plan, private sector projects and other forms of intervention in the space, taking into account urban expansion, a process linked to metropolization. The Maicá quilombola, in Santarém, has a somewhat peculiar history in relation to their territory of origin, which has resulted in land conflicts. Even in the midst of constant struggle, the identity of this group is consolidated, culminating in the titling of their lands, however, the pressure they suffer from the metropolis puts the members of this ethnically configured territory into question. Using a methodology based on explanatory research through qualitative analysis, it was possible to observe the numerous impacts on the territory in question and their effects, which contribute, paradoxically, both to strengthening and weakening the quilombola identity. The prospect of new conflicts appears in the conclusive horizon of the research, in which it is considered that the Maicá quilombo will be destined to fight for its territory for a long time to come.
Keywords: Território; Impactos sócio territoriais; Identidade; Santarém/PA; CIÊNCIAS HUMANAS